DNA Fragmentation and mRNA Expression of Bcl-2, Bcl-xL, p53, p21 and HSP70 Genes in Nondysplastic and Dysplastic Oral Lichen Planus - Abhishek Jana; Jincy Thomas; Pratiti Ghosh (Wolters Kluwer Medknow Publications, 2022)
Background: Oral lichen planus (OLP) is a chronic inflammatory disease. Apoptosis of the basal keratinocytes is a causative factor for OLP pathogenesis but the detailed mechanism of apoptosis among nondysplastic and dysplastic OLP lesions is yet unraveled. Aims: This study aims to evaluate the involvement of cellular DNA fragmentation and alteration in the expression of Bcl-2 and B-cell lymphoma extra-large (Bcl-xL), p53, p21 and heat shock protein 70 (HSP70) in nondysplastic and dysplastic OLP lesions. Materials and Methods: Untreated, fifteen OLP patients each with nondysplastic and dysplastic lesions were enrolled for this study. Their DNA fragmentation was analyzed by the agarose gel electrophoresis method. The mRNA expression of Bcl-2, Bcl-xL, p53, p21 and HSP70 were measured using semi-quantitative reverse transcription-polymerase chain reaction. Results: Elevated DNA fragmentations were found in dysplastic lesions compared to nondysplastic type. Significantly higher expression of Bcl-2, Bcl-xL, p53 and p21 were found in both types of OLP lesion compared to the control. Expression of Bcl-2 and Bcl-xL were significantly elevated in nondysplastic lesions, whereas significantly overexpression of p53 and p21 were found in dysplastic lesions. Anti-stress protein HSP70 was overtly expressed in dysplastic lesions compared to other groups. Conclusion: Reduced expression of Bcl-2 and Bcl-xL, with elevated DNA fragmentation, may be associated with increased apoptosis in dysplastic lesions which aid in the resolution of the chronic inflammatory process. Higher expression of p53 and p21 in dysplastic lesions reflect its malignant potentiality. Overexpression of HSP70 in dysplastic lesions is a useful marker for higher cellular stress.